Fucosylated ubiquitin and orthogonally glycosylated mutant A28C: conceptually new ligands for Burkholderia ambifaria lectin (BambL). Issue 47 (4th November 2020) - Kuhaudomlarp, Sakonwan; Cerofolini, Linda; Santarsia, Sabrina; Gillon, Emilie; Fallarini, Silvia; Lombardi, Grazia; Denis, Maxime; Giuntini, Stefano; Valori, Carolina; Fragai, Marco; Imberty, Anne; Dondoni, Alessandro; et al.
Abstract : Metal free click reactions used to glycosylate ubiquitin and its mutant A28C afforded two protein scaffolds with high affinity for Burkholderia ambifaria lectin (BambL). Abstract : Two orthogonal, metal free click reactions, enabled to glycosylate ubiquitin and its mutant A28C forming two protein scaffolds with high affinity for BambL, a lectin from the human pathogen Burkholderia ambifaria . A new fucoside analogue, with high affinity with BambL, firstly synthetized and co-crystallized with the protein target, provided the insights for sugar determinants grafting onto ubiquitin. Three ubiquitin-based glycosides were thus assembled. Fuc-Ub, presented several copies of the fucoside analogue, with proper geometry for multivalent effect; Rha-A28C, displayed one thio-rhamnose, known for its ability to tuning the immunological response; finally, Fuc-Rha-A28C, included both multiple fucoside analogs and the rhamnose residue. Fuc-Ub and Fuc-Rha-A28C ligands proved high affinity for BambL and unprecedented immune modulatory properties towards macrophages activation.